Synthesis, characterization, and catalytic performance of Ni supported on sustainable POFA-derived SBA-15 for hydrogen-rich syngas from CO2 reforming of methane - Hasnain, Syed Muhammad Wajahat ul; Farooqi, Ahmad Salam; Victor Ayodele, Bamidele; Setiabudi, Herma Dina; Farooqi, Abid Salam; Alshareef, Rayed S.; Bawadi, Abdullah (Korean Society of Industrial Engineering Chemistry, 2024)
Palm Oil Fuel Ash (POFA) is massively produced by numerous palm oil mills worldwide, creating an environmental waste disposal problem. Notably, POFA serves as a cost-effective alternative silica source instead of the expensive tetraethyl orthosilicate (TEOS). This research focused on synthesizing SBA-15 from POFA waste and examining the effect of promoters on POFA-derived SBA-15-supported Ni-based catalysts. The 10 wt% Ni/SBA-15-POFA catalyst was sequentially impregnated with promoters having 1 wt% loading of Zr, Ce, La, and Cr. The catalysts were tested for CO2 methane reforming (CMR) at 800 °C for 8 hours while maintaining a stoichiometric feed ratio. Various characterization techniques, including XRD, FESEM, XPS, H2-TPR, CO2-TPD, and BET analysis were employed to assess the catalyst physicochemical properties. The addition of promoter changed the properties of catalyst. Except for Cr-promoted catalyst, the addition of promoters positively impacted catalytic performance, activity, and stability. XRD analysis showed that Cr addition had detrimental effects on the crystallite structure of the Ni/SBA-15-POFA catalyst. In contrast, Zr, Ce, and La additions significantly reduced the crystallite size and improved active metal dispersion. Overall, the Zr-promoted catalyst exhibited the best performance in terms of activity and stability, with a CH4 conversion of 90 % and CO2 conversion of 94.4 %. The spent catalyst characterization, including XRD, FESEM, O2-TPO, and RAMAN, showed that promoter addition significantly reduced carbon deposition. The stable and superior perfromance of Zr-promoted catalyst was attributed to the production of MWCNTs. Conversely, the rapid deactivation of the unpromoted catalyst may be due to the formation of amorphous carbon, which tends to quickly block active sites and reduce the catalytic activity.